2017
DOI: 10.1542/peds.2016-3119
|View full text |Cite
|
Sign up to set email alerts
|

Incentive-based Intervention to Maintain Breastfeeding Among Low-income Puerto Rican Mothers

Abstract: BACKGROUND AND OBJECTIVE: Despite maternal and child health benefits, breastfeeding rates are relatively low among low-income Puerto Rican mothers. This study examined the hypothesis that monthly financial incentives would significantly increase the proportion of breastfeeding mothers at 6 months postpartum compared with Supplemental Nutrition Program for Women, Infants, and Children (WIC) services only among Puerto Rican mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 57 publications
1
69
0
Order By: Relevance
“…A few studies reported a declining of the intervention effect over time (Ahmed, Roumani, Szucs, Zhang, & King, 2016;Aksu et al, 2011;Washio et al, 2017). Similarly, this meta-analysis revealed weaker intervention effects on exclusive breastfeeding beyond thirteen weeks postpartum.…”
Section: Sustainability Of Intervention Effectmentioning
confidence: 55%
See 1 more Smart Citation
“…A few studies reported a declining of the intervention effect over time (Ahmed, Roumani, Szucs, Zhang, & King, 2016;Aksu et al, 2011;Washio et al, 2017). Similarly, this meta-analysis revealed weaker intervention effects on exclusive breastfeeding beyond thirteen weeks postpartum.…”
Section: Sustainability Of Intervention Effectmentioning
confidence: 55%
“…There were also promising BCTs, which need to be further investigated, such as 'material incentive', and 'material reward'. For example, one study (Washio et al, 2017) demonstrated the effectiveness of financial incentives provided within one month after delivery for promoting exclusive breastfeeding. Payments were provided at each session and for up to six months if breastfeeding was demonstrated in front of an expert.…”
Section: Bcts Used In the Interventionsmentioning
confidence: 99%
“…Offering incentives to women to breast feed have been identified as an effective intervention to increase breast feeding and have been implemented in the USA,4 France5 and Canada 6. The first ever randomised controlled trial (RCT) of a financial incentive for breast feeding was conducted among 36 low-income Puerto Rican mothers who had initiated breast feeding.…”
Section: Introductionmentioning
confidence: 99%
“…The first ever randomised controlled trial (RCT) of a financial incentive for breast feeding was conducted among 36 low-income Puerto Rican mothers who had initiated breast feeding. This US-based RCT found higher rates of continued breast feeding in the intervention group compared with control (89% vs 44% at 1 month; 89% vs 17%, at 3 months; 72% vs 0%, at 6 months) 4. The authors recommended large-scale studies to assess clinical and cost-effectiveness of incentive-based breastfeeding interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Make no mistake: Dr Washio and colleagues 1 have courageously conducted a trial about which many have whispered but few have dared to have open discussions. Paying women to breastfeed is a strategy that most investigators have assiduously avoided.…”
mentioning
confidence: 99%